Complement C3F allotype synthesized by liver recipient modifies transplantation outcome independently from donor hepatic C3. Issue 1 (25th November 2016) - Valero‐Hervás, Diana María; Sánchez‐Zapardiel, Elena; Castro, María José; Gallego‐Bustos, Fernando; Cambra, Félix; Justo, Iago; Laguna‐Goya, Rocío; Jiménez‐Romero, Carlos; Moreno, Enrique; López‐Medrano, Francisco; San Juan, Rafael; Fernández‐Ruiz, Mario; et al.
Abstract: Complement component 3 (C3) presents both slow (C3S) and fast (C3F) variants, which can be locally produced and activated by immune system cells. We studied C3 recipient variants in 483 liver transplant patients by RT‐PCR‐HRM to determine their effect on graft outcome during the first year post‐transplantation. Allograft survival was significantly decreased in C3FF recipients (C3SS 95% vs C3FS 91% vs C3FF 83%; P =.01) or C3F allele carriers (C3F absence 95% vs C3F presence 90%, P =.02). C3FF genotype or presence of C3F allele independently increased risk for allograft loss (OR: 2.38, P =.005 and OR: 2.66, P =.02, respectively). C3FF genotype was more frequent among patients whose first infection was of viral etiology (C3SS 13% vs C3FS 18% vs C3FF 32%; P =.04) and independently increased risk for post‐transplant viral infections (OR: 3.60, P =.008). On the other hand, C3FF and C3F protected from rejection events (OR: 0.54, P =.03 and OR: 0.63, P =.047, respectively). Differences were not observed in hepatitis C virus recurrence or patient survival. In conclusion, we show that, independently from C3 variants produced by donor liver, C3F variant from recipient diminishes allograft survival, increases susceptibility to viral infections, and protects from rejection after transplantation. C3 genotyping of liver recipients may be useful to stratify risk.